Routledge Handbook of Global Land and Resource Grabbing - Andreas Neef; Chanrith Ngin; Tsegaye Moreda; Sharlene Mollett (Routledge, 2023)
This handbook provides a cutting-edge, comprehensive overview of global land and resource grabbing. Global land and resource grabbing has become an increasingly prominent topic in academic circles, among development practitioners, human rights advocates, and in policy arenas. The Routledge Handbook of Global Land and Resource Grabbing sustains this intellectual momentum by advancing methodological, theoretical and empirical insights. It presents and discusses resource grabbing research in a holistic manner by addressing how the rush for land and other natural resources, including water, forests and minerals, is intertwined with agriculture, mining, tourism, energy, biodiversity conservation, climate change, carbon markets, and conflict. The handbook is truly global and interdisciplinary, with case studies from the Global South and Global North, and chapter contributions from practitioners, activists and academics, with emerging and Indigenous authors featuring strongly across the chapters. The handbook will be essential reading for students and scholars interested in land and resource grabbing, agrarian studies, development studies, critical human geography, global studies and natural resource governance.
Keywords: 300; biodiversity; climate; conservation; global; land; natural resources; policy; resources; resource grabbing